(untitled) (Journal of Parents and Teachers, 2026)
The experience shared by Mr Ricardo San Martín, a teacher at the I.B. Alfonso XI in Alcalá la Real, regarding the English seminar he runs, is quite unique. It is a seminar broadcast via the school’s own radio station. It all began with Mr San Martín’s interest in amateur radio, which led him to recognise this form of communication as an important teaching tool. The proposal proved very appealing to the pupils and, little by little, with the support of the School Council, they were able to acquire the necessary equipment. Once they had mastered the technical aspects, the pupils had the opportunity to communicate with pupils from other countries, in English of course, making it an excellent way to practise the language.